2010
DOI: 10.1016/j.jmb.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Compensated Pathogenic Deviations: Analysis of Structural Effects

Abstract: Pathogenic deviations (PDs) in humans are disease-causing missense mutations. However, in some cases, these disease-associated residues occur as the wild-type residues in functionally equivalent proteins in other species and these cases are termed 'Compensated Pathogenic Deviations' (CPDs). The lack of pathogenicity in a non-human protein is presumed to be explained in most cases by the presence of compensatory mutations, most commonly within the same protein. Identifying structural features of CPDs, and detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…CPDs tend to be less severe in terms of the difference in physicochemical properties between the substituted and substituting amino acids than is normally the case for pathological mutations [Barešić et al, 2010;Ferrer-Costa et al, 2007]. In the context of human disease, Suriano et al [2007] have provided a good example of the influence of compensated and compensating mutations in the OTC gene.…”
Section: Compensated Pathogenic Deviationsmentioning
confidence: 99%
“…CPDs tend to be less severe in terms of the difference in physicochemical properties between the substituted and substituting amino acids than is normally the case for pathological mutations [Barešić et al, 2010;Ferrer-Costa et al, 2007]. In the context of human disease, Suriano et al [2007] have provided a good example of the influence of compensated and compensating mutations in the OTC gene.…”
Section: Compensated Pathogenic Deviationsmentioning
confidence: 99%
“…In evolution, compensatory mutations are unlikely to occur singly; indeed, Poon et al [2005] have suggested that an average of 11.8 compensatory mutations may interact epistatically with a given deleterious mutation so as to restore wild-type levels of fitness. CPDs tend to be less severe in terms of the physicochemical difference between the substituted and substituting amino acids than normally pathological mutations [Barešić et al, 2009;FerrerCosta et al, 2007]. Barešić et al [2009] have also shown that amino acid residues surrounding the compensated residue in the folded protein are mutated more often than residues surrounding an uncompensated mutation, consistent with the view that compensation relies upon structurally local mutations.…”
Section: Discussionmentioning
confidence: 87%
“…However, while it is theoretically possible that a single mutation could do so, compensation of a clash is most likely to be achieved by making a number of smaller changes. Both Ferrer-Costa et al (33) and Barešić et al (10) found that CPDs have a higher average solvent accessibility. In other words, they are much more likely to be found on, or near, the protein surface.…”
Section: Properties Of Compensated Mutations and Mechanisms Of Compenmentioning
confidence: 96%
“…Restoring protein stability and hence regulated activity, will often need compensatory mutations that restore stability to the acceptable range of free energies. From a structural analysis perspective, compensated mutations are preferentially on the protein surface (10,33). As shown by Poon et al (24), compensatory events are most commonly intragenic, so the surface location is likely to be a result of it being easier to accumulate compensatory events (probably before the CPD mutation occurs) rather than it being anything to do with interactions with other proteins.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation